Strain-stress experimental behaviour of tapered columns in single-span frames/Trapecinių kolonų vienanaviuose rėmuose deformacijų-įtempių būvis - Šapalas, Vaidotas (Journal of Civil Engineering and Management, 2000)
Two single-span frame tests were carried out. The width of frame is 6m, column’s height 4.17m. Frame supports are pinned. Connection between column and beam is rigid. Beam of the frame was loaded with two vertical and one horizontal loads. The stability of tappered columns was analysed in frame plane and in perpendicular plane, according to [1] and [2] methods. All deflections were calculated taking into account support movements. During the first frame test R1-1 the tapered column collapsed at the load 2V=400kN and H=200 kN (vertical and horizontal loads). During the second test R1-2 the tapered column collapsed at the load 2V=390 kN and H=175 kN. In both tests columns collapsed in lateral-torsional buckling way. Because the column’s web is very thin at the load 2V=300 kN and H=150 kN the column’s web achieved local buckling. But the column was still carrying the load. During both tests at the load 2V=300 kN and H=150 kN the column began to twist in the middle of its height about the longitudinal axis and to bend about the weak axis. In test R1-1, the vertical experimental deflection (in point 6, see Fig 1 a) is about 17.5% smaller than the theoretical one. The horizontal experimental deflection (in point, see Fig 1 a) is about 11.6% smaller than the theoretical one. In test R1-2, vertical experimental deflection (in point 6, see Fig 1 a) is about 21.1% bigger than the theoretical one. The horizontal experimental deflection (in point, see Fig 1 a) is about 29.6% smaller than the theoretical one. In test R1-1, an experimental compression stresses in section A-A (see Fig 2) are about 11.2% smaller than the theoretical one. Experimental tension stresses in section A-A are about 8.65% smaller than the theoretical one. In test R1-2, an experimental compression stresses in section A-A is about 0.43% bigger than the theoretical one. An experimental tension strain in section A-A is about 1.73% smaller than the theoretical one. Article in Lithuanian. First Published Online: 26 Jul 2012